Idealized simulations reveal the potential for widespread high supersaturation in marine tropical deep convection - Chunying Fan; Siwei Li; Lin Zang; Zengxin Pan; Feiyue Mao; Fan Liu; Wei Gong; Daniel Rosenfeld (Atmospheric Research, 2026)

Hydroclimatic trend and millennial abruptions in southwestern China since the last deglaciation - Yan Yang; Hai Xu; Jing Wang; Ye Yang; Yunping Song; Jin Zhang; Siwei Shi; Yanpeng Li; Lin Shi; Kaiyang He; Yu Feng; Sheng Xu (Global and Planetary Change, 2026)

Enhancing freeze-thaw tolerance in pre-fermented frozen dough: The role of mixing temperature and proofing degree - Lu Lu; Siwei Wang; Jing Peng; Qinlu Lin (Food Chemistry, 2026)

Effects of sugar alcohols on freeze-thaw tolerance of frozen dough: Focus on ice crystal growth, fermentation properties and gluten aggregation - Longfei Yang; Siwei Wang; Lu Lu; Jing Peng; Huaxi Xiao; Yue Wu; Xinli Yin; Jijun Gong; Qinlu Lin (Food Chemistry, 2026)

Mechanical behavior and design of an eight-bolt extended stiffened end-plate connection with oversized holes: Experimental and numerical studies - Bin Jiang; Liping Duan; Siwei Lin; Jiming Liu; Ge Qu; Jincheng Zhao (Engineering Structures, 2026)

Brick-and-mortar engineered Trimethoxy (2-phenylethyl) silane@h-BN/polyarylate nanofiber paper with ultrahigh thermal conductivity and dielectric strength - Jingxian Wang; Xueyang Liu; Yixuan Lin; Junjie Wang; Hanwen Zhang; Luoxin Wang; Hua Wang; Siwei Xiong (Chemical Engineering Journal, 2026)

Nano-GlycOTAC eradicates Mycobacterium tuberculosis biofilms and rectifies iron metabolism to augment host antimicrobial immunity - Zhuojun He; Deliang Liu; Yang Zhou; Yao Zhao; Guiqin Dai; Zhiqiang Lin; Siwei Zhang; Xiafei Dai; Yuying Chen; Jinzhi Pan; Huiling Liu; Hong Yu; et al. (Chemical Engineering Journal, 2026)

Functional characterization of TNF receptor-associated factor 7 in immune response and apoptotic regulation in Nile tilapia (Oreochromis niloticus) - Huaqing Sun; Chaoli He; Yujie Wang; Huiyan Lin; Lu Zhang; Xiaonuan Li; Xintong Zhen; Siwei Li; Jianmin Ye; Bingxi Li (Aquaculture, 2026)

Dihydroartemisinin targets ANXA2 to suppress hepatocellular carcinoma angiogenesis through the PI3K/AKT signaling pathway - Lulu Cao; Lihui Wang; Jun Lin; Jian Zhao; Bolun Xu; Jianxin Chen; Juanjuan Hu; Siwei Wang; Junhua Yu (Tissue and Cell, 2025)

Multi-scale quantitative analysis of grotto sandstone degradation considering inorganic salt phase transitions - Sicheng Lin; Luqi Wang; Wengang Zhang; Shuo Wang; Zihua Xiong; Siwei Jiang; Gang Zhao (International Journal of Rock Mechanics and Mining Sciences, 2025)

Mechanochemical synthesis of ZnO@TiO2 II heterojunction material: Photocatalytic degradation and antibacterial synergistic effect - Juan Pei; Xiaoling Wan; Mingxing Guo; Jialan Mi; Wei Wu; Ying Hong; Pei Hu; Ping Chen; Lin Chen; Siwei Xiang; Qianyu Zhang; Haichun Zeng; et al. (Chemical Engineering Journal, 2025)

Metabolic Control of Stem Cell Function: Insights into Amino Acid-Driven Mechanisms - Jiawei Zeng; Xiaohao Liu; Jiaming Bi; Chuzi Mo; Han Zhang; Yan Chai; Yunhe Lin; Siwei Li; Zhongjun Liu; Mingyan Yao; Shuaimei Xu; Peiyan Yuan (Stem Cell Reviews and Reports, 2025)

UV/green rust/glucose oxidase-based Fenton-like Systems for algal removal: Mechanisms of sustained oxidative capacity in UV-enhanced systems - Siwei Li; Qian Zhang; Meng Li; Xiangyu Liu; Jie Peng; Bing Lin; Jialong Huang; Yong Huang (Journal of Environmental Chemical Engineering, 2025)

Isolation, characterization, and biotechnological application of novel glutaminase-producing Bacillus strain for quality enhancement in soy sauce - Chen Siwei; Huang Jialiang; Liu Heng; Zhang Xiao; Xu Ting; Luo Lin; Chen Sui; Xu Zhenlin; Zhou Kai (Food Bioscience, 2025)

Involving degradation products provides a new perspective of diffuse pollution assessment of atrazine with a modified mass balance approach - Zewei Guo; Wei Ouyang; Mengchang He; Siwei Peng; Jingyi Hu; Chunye Lin (Journal of Hazardous Materials, 2025)

Mechanical performance and design method of a stiffened T-stub with four-row bolts and oversized holes - Bin Jiang; Liping Duan; Siwei Lin; Yan Zhu; Jiming Liu; Jincheng Zhao (Engineering Structures, 2025)

Retrieving aerosol single scattering albedo from FY-3D observations combining machine learning with radiative transfer model - Qingxin Wang; Siwei Li; Zhaoyang Zhang; Xingwen Lin; Yanmin Shuai; Xinyan Liu; Hao Lin (Atmospheric Research, 2025)

Direct solar radiation distribution and driving mechanisms on planetary surfaces – Moon, Mars, Ceres, and Mercury - Siwei Lin; Xianyan Wang; Nan Chen (Icarus, 2025)

Influence of Electrode Size on the Fragmentation Process of Rocks with Different Heterogeneities under High-Voltage Pulses - Yong Zhao; Yi Liu; Hongbin Liao; Tianyu Wang; Siwei Liu; Fuchang Lin (Rock Mechanics and Rock Engineering, 2025)

Exploring the impact of visible light intensity on algae-bacterial symbiotic system treating aniline wastewater: Performance, microbial community and metabolic pathways - Jiajing Chen; Qian Zhang; Meng Li; Jing He; Bing Lin; Nanping Wu; Xunhao Liu; Siwei Li; Jialong Huang; Xiaoqian Dong; Hongyu Wang (Journal of Water Process Engineering, 2024)

Late Triassic orogenic gold mineralization along the northwest margin of the Indochina Block: Revealed from calcite U-Pb ages and geochemistry of the Phapon gold deposit, Laos - Linnan Guo; Yanwen Tang; Lin Hou; Shusheng Liu; Chunmei Huang; Zhiwei Han; Siwei Xu; Zhibo Luo; Huimin Liang (Journal of Asian Earth Sciences, 2024)

Cross-Scale Quantitative and Qualitative Study of Grotto Sandstone Under Salt Weathering - Sicheng Lin; Luqi Wang; Wengang Zhang; Shuo Wang; Kaiqiang Zhang; Yu Lei; Siwei Jiang; Huili Chen; Gang Zhao; Xuemei Feng (Rock Mechanics and Rock Engineering, 2024)

Variations of silicon species, dissolution and crystallinity within sichars prepared under different heating rate - Siwei Guo; Huili Zeng; Xiaomin Zhu; Lin Liu; Baoliang Chen; Xin Xiao (Science of The Total Environment, 2024)

Research on the wear resistance and impact resistance of modified rubberized concrete - Shucheng Yuan; Fengyu Zhang; SiWei Du; Kunpeng Li; Jiale Luo; Yuancong Liu; Zhanyuan Zhu; Jiangfeng Dong; Wei Liang; Jincheng Lin (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Biofiltration matrix optimization for efficient nitrogen removal from domestic onsite wastewater - Siwei Chen; Mian Wang; Danny Lin; Frank M. Russo; Christopher J. Gobler; Xinwei Mao (Journal of Water Process Engineering, 2024)

Slope unit-based genetic landform mapping on Tibetan plateau- a terrain unit-based framework for large spatial scale landform classification - Siwei Lin; Xianyan Wang; Chen Nan (CATENA, 2024)

Blue polyimides for high-performance solution-processable organic light-emitting diodes - Wenhui Wang; Kaijin Chen; Chuying Li; Faxu Lin; Yuxuan Li; Yubo Long; Juan Zhao; Siwei Liu; Zhenguo Chi; Jiarui Xu; Yi Zhang; Yuguang Ma (Chemical Engineering Journal, 2024)

Herbaceous ornamental plants with conspicuous aesthetic traits contribute to plant invasion risk in subtropical urban parks - Siwei Hu; Cheng Jin; Ruiyan Liao; Li Huang; Lihua Zhou; Yuxiao Long; Min Luo; C.Y. Jim; Wenhao Hu; Dunmei Lin; Shengbin Chen; Changjing Liu; et al. (Journal of Environmental Management, 2023)

Relationship between night shift and sleep problems, risk of metabolic abnormalities of nurses: a 2 years follow-up retrospective analysis in the National Nurse Health Study (NNHS) - Heli Zhang; Jingpin Wang; Siwei Zhang; Sumei Tong; Jinping Hu; Ying Che; Lin Zhuo; Peng Wang; Rongmei Geng; Yujie Zhou; Panfeng Wang; Siyan Zhan; et al. (International Archives of Occupational and Environmental Health, 2023)
Background and purpose Efforts to improve nurses’ physical and mental health are critical to ensuring the safety and quality of the healthcare system. Long-term studies targeting the relevancy of nurses’ occupation characteristics with health conditions remain insufficient. This study aimed to examine the relationship between nurses’ night shift and sleep problems and metabolic abnormalities risk. Methods This study was a part of the National Nurse Health Study, an ambispective cohort study in China, in 2021. Based on an integration physical examination data system, this study carried out a retrospective analysis of 730 nurses from 2018 to 2020 and combined with a questionnaire survey in 2021. The STROBE guidelines were adopted for reporting. Results In the 23 (23.0, 24.0) months follow-up, higher night shift load was associated with more sleep problems such as shortened sleep duration, sleep disorders, poor sleep quality, and sleep deprivation. Moreover, night shift load was associated with chronic diseases risk factors, increasing body mass index and body fat, with more night shift density, increasing the occurrence of low levels of high-density lipoprotein cholesterol, high triglyceride, triglyceride/high-density lipoprotein cholesterol ratio, and serum uric acid. Conclusion The night shift load has become an occupational health concern, contributing to chronic diseases relevant metabolic risk factors and negative influence on sleep health. Focus on the strategies to improve the sleep quality of nurses undergoing night shift work, optimize work scheduling and ongoing monitor the relevant risk factors are essential to enhance the stability and well-being of the nursing workforce. Clinical Trials registration information: NCT04572347, on October 1, 2020. https://www.clinicaltrials.gov/ct2/show/NCT04572347

Long-term PM2.5 concentration prediction based on improved empirical mode decomposition and deep neural network combined with noise reduction auto-encoder- A case study in Beijing - Mengfan Teng; Siwei Li; Jie Yang; Shuo Wang; Chunying Fan; Yu Ding; Jiaxin Dong; Hao Lin; Shansi Wang (Journal of Cleaner Production, 2023)

Exploring watershed structural variation during watershed evolution process under artificial rainfall experiment - Siwei Lin; Nan Chen (Earth Science Informatics, 2023)

In situ geochemistry and Fe–O isotopic composition of iron oxides from the Pha Lek Fe deposit, northwest Truong Son orogenic belt, Laos: implications for ore-forming processes - Lin Hou; Linnan Guo; Siwei Xu; Qiming Zhang; Xiangting Zeng (Mineralium Deposita, 2021)

Spatial distribution of n-alkanes in surface sediments of Selin Co Lake, central Tibetan Plateau, China - Qiangqiang Kou; Xiao Lin; Junbo Wang; Siwei Yu; Jinlei Kai; Andreas Laug; Liping Zhu (Journal of Paleolimnology, 2021)

Available soil nutrients and water content affect leaf nutrient concentrations and stoichiometry at different ages of Leucaena leucocephala forests in dry-hot valley - Yongming Lin; Aimin Chen; Siwei Yan; Loretta Rafay; Kun Du; Daojie Wang; Yonggang Ge; Jian Li (Journal of Soils and Sediments, 2019)

Geology, Geochronology, and Hf Isotopic Composition of the Pha Lek Fe Deposit, Northern Laos: Implications for Early Permian Subduction-Related Skarn Fe Mineralization in the Truong Son Belt - Lin Hou; Shusheng Liu; Linnan Guo; Fuhao Xiong; Chao Li; Meifeng Shi; Qiming Zhang; Siwei Xu; Songyang Wu (Journal of Earth Science, 2019)